A critical realist theory of ideology: Promoting planning as a vanguard of societal transformation. (May 2022) - Xue, Jin
This article explores the potential values of a critical realist theory of ideology on the analysis of planning issues. In particular, it argues its usefulness in promoting planning as a vanguard of societal transformation. The critical realist theory of ideology revitalizes the epistemological inquiry of beliefs, which enables an evaluation of the social, economic and environmental impacts of the ideas and beliefs embedded in planning. Furthermore, the essence of critical realist theory of ideology is to explain the (re)production of the ideology, which paves the way for transformative planning, as transformation cannot be realized without eliminating constraining social conditions. Finally, critical realism situates its critique of ideology within the wider transformation process by rendering visible the dimensions that can contribute to eradicating the ideology in question, and shaping better planning ideas, including ethical reasoning, utopia thinking and transformative agency. A meta-theoretical framework based on critical realism is proposed to guide a critique of ideology in planning. By using an example of planning for sustainable urban development in Copenhagen and Oslo, the paper demonstrates the ways in which the meta-theoretical framework can be applied to planning in a quest for societal transformation.